2021
DOI: 10.1111/wrr.12914
|View full text |Cite
|
Sign up to set email alerts
|

Use of a negative pressure wound therapy system over closed incisions option in preventing post‐sternotomy wound complications

Abstract: Post-sternotomy surgical site infections may be serious complications responsible for increased morbidity, mortality and length of hospital stay. A variety of wound-healing strategies can be used over closed surgical incisions, including negative pressure wound therapy (NPWT). The aim of the study is to assess sternal wound complica-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Aside from potential life-threatening consequences, SWI is associated with a prolonged length of stay (LOS) in the hospital and, according to the European Health Service, may add an estimated 19 billion Euros of additional health care costs [ 2 ]. It has been previously demonstrated that avoiding virulent bacterial contamination that can lead to mediastinitis and the degradation of sutured skin, especially in high-risk patients, is integral to helping prevent postoperative complications associated with SWI [ 3 , 4 ]. This postoperative complication is most prevalent in patients with a medical history of obesity, diabetes, chronic obstructive pulmonary disease (COPD) and advanced age [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aside from potential life-threatening consequences, SWI is associated with a prolonged length of stay (LOS) in the hospital and, according to the European Health Service, may add an estimated 19 billion Euros of additional health care costs [ 2 ]. It has been previously demonstrated that avoiding virulent bacterial contamination that can lead to mediastinitis and the degradation of sutured skin, especially in high-risk patients, is integral to helping prevent postoperative complications associated with SWI [ 3 , 4 ]. This postoperative complication is most prevalent in patients with a medical history of obesity, diabetes, chronic obstructive pulmonary disease (COPD) and advanced age [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…One hundred and ninety-one studies were retrieved from a systematic literature search ( Supplementary Materials Figure S1 ). Ten studies [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] fulfilled the inclusion criteria. Their data are summarized in Table 2 and Supplementary Table S3 .…”
Section: Resultsmentioning
confidence: 99%
“… Forest plots of study interventions and outcomes [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. …”
Section: Figurementioning
confidence: 99%
“…Brega et al [ 23 ] analyzed 90 patients undergoing cardiac surgery with a median sternal incision and found that, compared with conventional gauze, hydrocolloids, and carboxymethyl fibrin dressings, the patients who underwent NPWT at closed incisions had a significantly lower incidence of deep sternal complications than those who were administered conventional gauze, hydrocolloids, and carboxymethyl fibrin dressings. [ 23 ] The difference was obvious in patients with obesity. In a retrospective study, Bonds et al [ 24 ] analyzed 254 patients undergoing colorectal surgery and found that 69 (27.2%) developed SSIs, of which 4 (12.5%) occurred in patients receiving incision negative pressure therapy and 65 (29.3%) occurred in patients receiving a standard suture.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Several experiments have been carried out on the treatment of surgical incision and the reduction of infection and other complications with NWPT. Brega et al [23] analyzed 90 patients undergoing cardiac surgery with a median sternal incision and found that, compared with conventional gauze, hydrocolloids, and carboxymethyl fibrin dressings, the patients who underwent NPWT at closed incisions had a significantly lower incidence of deep sternal complications than those who were administered conventional gauze, hydrocolloids, and carboxymethyl fibrin dressings. [23] The difference was obvious in patients with obesity.…”
Section: Discussionmentioning
confidence: 99%